Epigenetics Theoretical Limits of Synthetic Genomes : The Cases of Artificials Caulobacter (C. eth-2.0), Mycoplasma Mycoides (JCVI-Syn 1.0, JCVI-Syn 3.0 and JCVI_3A), E-coli and YEAST chr XII (Global Journal of Science Frontier Research, 2022)
Abstract not found
Keywords: synthetic genomes; epigenetics; transposons; biomathematics; fibonacci numbers